Alternative mechanisms of increased eggshell hardness of avian brood parasites relative to host species - Igic, Branislav (The Royal Society, 2011)
Obligate brood parasitic birds lay their eggs in nests of other species and parasite eggs typically have evolved greater structural strength relative to host eggs. Increased mechanical strength of the parasite eggshell is an adaptation that can interfere with puncture ejection behaviours of discriminating hosts. We investigated whether hardness of eggshells is related to differences between physical and chemical traits from three different races of the parasitic common cuckoo Cuculus canorus, and their respective hosts. Using tools developed for materials science, we discovered a novel correlate of increased strength of parasite eggs: the common cuckoo's egg exhibits a greater microhardness, especially in the inner region of the shell matrix, relative to its host and sympatric non-host species. We then tested predictions of four potential mechanisms of shell strength: (i) increased relative thickness overall, (ii) greater proportion of the structurally harder shell layers, (iii) higher concentration of inorganic components in the shell matrix, and (iv) elevated deposition of a high density compound, MgCO(3), in the shell matrix. We confirmed support only for hypothesis (i). Eggshell characteristics did not differ between parasite eggs sampled from different host nests in distant geographical sites, suggesting an evolutionarily shared microstructural mechanism of stronger parasite eggshells across diverse host-races of brood parasitic cuckoos.